Budgetary impact of diagnostic tests for visceral leishmaniasis in Brazil - Tália Santana Machado de Assis; André Luís Ferreira de Azeredo-; Diana Oliveira; Gláucia Cota; Guilherme Loureiro Werneck; Ana Rabello (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: The aim of the present study was to estimate the financial costs of the incorporation and/or replacement of diagnostic tests for human visceral leishmaniasis (VL) in Brazil. The analysis was conducted from the perspective of the Brazilian Unified National Health System (SUS) over a period of three years. Six diagnostic tests were evaluated: the indirect immunofluorescence antibody test (IFAT), the IT LEISH rapid test, the parasitological examination of bone marrow aspirate, the direct agglutination test (DAT-LPC) standardized in the Clinical Research Laboratory, René Rachou Institute of the Oswaldo Cruz Foundation, the Kalazar Detect rapid test, and polymerase chain reaction (PCR). The assumptions used were the number of suspected cases of VL reported to the Brazilian Ministry of Health in 2014 and the direct cost of diagnostic tests. The costs to diagnose suspected cases of VL over three years using the IFAT and the DAT-LPC were estimated at USD 280,979.91 and USD 121,371.48, respectively. The analysis indicated that compared with the use of the IFAT, the incorporation of the DAT-LPC into the SUS would result in savings of USD 159,608.43. With regard to the budgetary impact of rapid tests, the use of IT LEISH resulted in savings of USD 21.708,72 over three years. Compared with a parasitological examination, diagnosis using PCR resulted in savings of USD 3,125,068.92 over three years. In this study, the replacement of the IFAT with the DAT-LPC proved financially advantageous. In addition, the replacement of the Kalazar Detect rapid test with the IT LEISH in 2015 was economically valuable, and the replacement of parasitological examination with PCR was indicated.